Project manager street smarts : a real world guide to PMP skills - Zaval, Linda Kretz, 1948- (Serious skills., 2011)
The perfect workbook for project managers and PMP exam candidates seeking practical experience New project managers and students pursuing the Project Management Professional certification are looking for practical experience to solidify their skills. The step-by-step tasks presented in this book offer them an opportunity to practice the common tasks project managers face in the real world. The authors, both expert project management trainers and consultants, explore each phase of project management: initiation, planning, execution, monitoring and control, and closing the project, with in-depth.